Testing the invariance of expectations models of inflation - Jennifer L. Castle; Jurgen A. Doornik; David F. Hendry; Ragnar Nymoen (University of Oslo, Department of Economics, 2010)
The new-Keynesian Phillips curve (NKPC) includes expected future inflation to explain current inflation. Such models are estimated by replacing the expected value by the future outcome, using Instrumental Variables or Generalized Method of Momentsmethods. However, the underlying theory does not allow for various non-stationarities-although crises, breaks and regimes shifts are relatively common. We analytically investigate the consequences for NKPC estimation of breaks in data processes, then apply the new technique of impulse-indicator saturation to salient published studies to check their viability. The coefficient of the future value becomes insignificant after modelling breaks.
Keywords: C51; C22; 330; New-Keynesian Phillips curve; Inflation expectations; Structural breaks; Impulse-indicator saturation